Effect of patient- and drug-specific barcode technology on medication dispensing errors in a specialty pharmacy. (21st September 2018) - Feinberg, B.; Burruss, R.; Wood, A.; Arikian, V.; Jaster, R.; Oleru, K.; Traurig, T.; Sutherland, B.; Nabhan, C.; Klink, A.
Abstract: Background: Patient medication safety is a major public health concern [1 ]. Therefore, a critical goal of the practice of pharmacy is to provide safe and efficacious medications which has been stated by all pharmacy regulatory boards, accreditation agencies, professional societies, the Institute of Medicine, the Institute for Safe Medication Practices, and others [1–4 ]. This is an important consideration for specialty pharmacies (SP), given that many of the medications they dispense are challenging and confusing to self-administer and store properly as well as quite expensive for health plans and patients. SP need to minimize medication misadventures by not just educating and clinically monitoring patients but must ensure that SP medications are dispensed without error (defects), including using appropriate dispensing system technology to support this. Objectives: The objective of this study was to determine if a specially designed prescription drug label, incorporating a barcode with both patient- and drug-specific identifiers, could reduce medication errors/defects unintentionally dispensed to the SP's patients and prescribers as compared to prescriptions dispensed with a traditional label without barcode. Methods: A retrospective, non-randomized review of all SP prescriptions, using a traditional prescription label (no barcode), dispensed from 11/1/16 to 12/31/16 was done to establish a baseline of total dispenses, the number of dispensed external drug defects or errors (EDDD), i.e., defects that got to a patient or prescriber, and the number of defects per million opportunities (DPMO). Then, from 1/1/17 to 3/31/17 a prospective, observational pilot program was implemented on a subset of all SP patients and therapies, e.g, primarily oncology, autoimmune, HIV, rheumatology, dermatology and others but excluding neurologic, psychiatric, analgesic and investigational drugs. In the pilot all prescription labels contained a barcode with patient- and drug-specific identifiers. For the purpose of the pilot, EDDD were not differentiated by type of defect or any specific patient intervention related to the defect; however, all EDDD were reviewed and acted upon by the Quality Management Team as part of a continuous quality management program, using Lean Six SigmaTM applications. A desired outcome of the pilot was achievement of 50% fewer DPMO than was calculated in the baseline study. The chi-square statistic without Yates Correction was used to determine if a difference existed between the baseline and pilot group, and an a priori level of statistical significance was established ( p < .05). Results: The baseline study resulted in 39, 923 total prescriptions dispensed with DPMO of 1603 (0.16% of DPMO). The pilot study resulted in 1968 prescriptions dispensed with DPMO of 508 (0.05% of DPMO). The reduction in DPMO in the pilot compared to baseline was 1095 (68.3% decrease) which was significant to p < .00001. Conclusions: The SP prescription label with a barcode containing patient- and drug-specific data significantly reduced the number of EDDD, improving medication-related patient/prescriber safety. Medication safety and continuous improvement of SP medication dispensing are critically important. This study suggests that use of the SP label with barcode might be expanded to include all other SP drug categories and should be studied accordingly.